Global Trends in Death, Years of Life Lost, and Years Lived With Disability Caused by Breast Cancer Attributable to Secondhand Smoke From 1990 to 2019 - Ou, Zejin; Gao, Yunxia; Jiang, Diwei; Cui, Jiaxin; Ren, Yixian; Tang, Shihao; Duan, Danping; Yu, Danfeng; Wang, Zhi (Frontiers in Oncology, 2022)
Background Secondhand smoke is an important risk factor to breast cancer patients’ survival. This article aimed to describe the epidemiological changes of health loss caused by female breast cancer attributable to secondhand smoke from 1990 to 2019. Methods Data on breast cancer was derived from the Global Burden of Disease study 2019. The epidemiological status and trends were estimated using the number, age-standardized rate (ASR), and estimated annual percentage change (EAPC). Results In 2019, secondhand smoke-related breast cancer caused 168.33×102 death, 5242.58×102 years of life lost (YLLs), and 334.03×102 years lived with disability (YLDs) globally. The overall ASR of death and YLLs caused by breast cancer attributable to secondhand smoke presented decreasing trends from 1990 to 2019, with the respective EAPCs of −0.78 and −0.87. Meanwhile, decreasing trends occurred in most geographic regions, particularly that of YLLs in high-income North America (EAPC = −3.35). At the national level, most countries/territories had decreasing trends of death and YLLs, particularly Denmark, in which the respective EAPCs were −4.26 and −4.64. However, the ASR of YLDs showed an increasing trend globally (EAPC = 0.32). Meanwhile, increasing trends were observed in most regions and countries, particularly the Solomon Islands and Lesotho, with the respective EAPCs being 6.18 and 4.33. The changing trends were closely associated with sociodemographic development. Conclusions Trends in secondhand smoke-related death and YLLs caused by breast cancer declined from 1990 to 2019. However, secondhand smoke remains a challenge to the patients’ longevity and quality of life. The findings informed strategies should be strengthened the control of secondhand smoking.